2010
DOI: 10.1517/14656566.2011.534780
|View full text |Cite
|
Sign up to set email alerts
|

Are there better Bcr-Abl kinase inhibitors for chronic myeloid leukaemia than imatinib?

Abstract: The Bcr-Abl kinase inhibitor imatinib is the standard treatment for chronic myeloid leukaemia (CML). Some subjects with CML do not respond to, or are intolerant of, imatinib. Nilotinib and dasatinib were initially developed to treat these subjects, and were shown to be effective. They are now being trialled as initial 'inib' treatment for CML. The objective was to evaluate the recent Phase III clinical trials comparing nilotinib or dasatinib with imatinib in newly diagnosed CML. Nilotinib and dasatinib were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Patients with sustained deep molecular responses achieved more frequently with second-generation TKIs, may be considered for treatment discontinuation [3, 4, 7]. Currently, the National Comprehensive Cancer Network (NCCN) recommend discontinuation for patients in stable molecular response (BCR-ABL1 ≤ 0.01% IS) for ≥ 2 years [8]. Early responses, including BCR-ABL1 ≤ 10% at 3 months, ≤ 1% at 6 months, ≤ 0.1% at 1 year, and ≤ 0.01% later on, have been associated with higher probability of eventually having successful treatment-free remission [9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with sustained deep molecular responses achieved more frequently with second-generation TKIs, may be considered for treatment discontinuation [3, 4, 7]. Currently, the National Comprehensive Cancer Network (NCCN) recommend discontinuation for patients in stable molecular response (BCR-ABL1 ≤ 0.01% IS) for ≥ 2 years [8]. Early responses, including BCR-ABL1 ≤ 10% at 3 months, ≤ 1% at 6 months, ≤ 0.1% at 1 year, and ≤ 0.01% later on, have been associated with higher probability of eventually having successful treatment-free remission [9].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, publications were identified that served as a basis for knowledge about the natural history of the disease and the technologies assessed. Publications were found that had the objective of assessing recent phase III clinical trials that compared nilotinib or dasatinib with imatinib in recently diagnosed CML (16)(17)(18).…”
Section: Clinical Datamentioning
confidence: 99%
“…The branch treated with imatinib was the least expensive option of the three. (12)(13)(14)(15)(16) From total costs, 7.56% was attributed to the treatment of this type of patient, 21.76% to the costs of the technologies analyzed, and adverse events represented 12.13% of the total cost in the different branches, while the remaining 58.55% were progression costs.…”
Section: Ethical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more serious complications are relatively rare, prolongation of the QT interval, acute renal failure, and development of Fanconi syndrome have been reported. [41][42][43][44] Some signaling pathways inhibited by these drugs are renoprotective in models of ischemia-reperfusion injury 18,20,24 ; therefore, if clinical trials of cABL inhibitors were to be implemented, renal function would need to be monitored closely. One study suggested a greater decline in renal function in patients who have CML and are treated long term with imatinib than that expected from aging alone.…”
mentioning
confidence: 99%